2018
DOI: 10.3389/fnagi.2018.00133
|View full text |Cite
|
Sign up to set email alerts
|

Brain Distribution and Modulation of Neuronal Excitability by Indicaxanthin From Opuntia Ficus Indica Administered at Nutritionally-Relevant Amounts

Abstract: Several studies have recently investigated the role of nutraceuticals in complex pathophysiological processes such as oxidative damages, inflammatory conditions and excitotoxicity. In this regard, the effects of nutraceuticals on basic functions of neuronal cells, such as excitability, are still poorly investigated. For this reason, the possible modulation of neuronal excitability by phytochemicals (PhC) could represent an interesting field of research given that excitotoxicity phenomena are involved in neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…These conditions contribute to oxidative stress and neural cell death, in which TG2 plays a key role [ 34 ]. It has been reported that hippocampal neurons are more responsive to indicaxanthin [ 36 ]. In particular, it has an important role in several metabolic functions both in vitro and in vivo, reducing inflammation and enhancing immune response [ 22 , 23 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions contribute to oxidative stress and neural cell death, in which TG2 plays a key role [ 34 ]. It has been reported that hippocampal neurons are more responsive to indicaxanthin [ 36 ]. In particular, it has an important role in several metabolic functions both in vitro and in vivo, reducing inflammation and enhancing immune response [ 22 , 23 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions contribute to oxidative stress and neural cell death, in which TG2 plays a key role [30]. It has been reported that hippocampal neurons are more responsive to Indicaxanthin [39]. In particular, it has an important role in several metabolic functions both in vitro and in vivo, reducing in ammation and enhancing immune response [22,23,40].…”
Section: Discussionmentioning
confidence: 99%
“…Over-eating and obesity are tightly linked to neurobiological, behavioral and cognitive factors such as mood status, addictive behavior, impulsivity and reward processing; cognitive control [19,20,[33][34][35][36][37][38][39][40]. Exploring the effects of external modifications to body homeostasis caused by nutritional, neurophysiological or pharmacological tools is a widely applied approach that provides evidence to fundamental processes of the nervous system [41][42][43]. In this context, although cognitive performance in obese people is far from being elucidated [44], obesity has been recently considered as a risk factor for cognitive impairments [45].…”
Section: Discussionmentioning
confidence: 99%